Case Report: Low cardiac output syndrome with multisystem complications following total repair of tetralogy of fallot - Nova Setia, Daendy; Tartila,; Prawira, Yogi (Frontiers in Pediatrics, 2026)
BackgroundTetralogy of Fallot (ToF) repair in infants may be complicated by low cardiac output syndrome (LCOS), which can precipitate rare multisystem complications. Junctional ectopic tachycardia (JET), atrial thrombosis, and cortical blindness are underrecognized sequelae requiring multidisciplinary management.Case presentationWe report a 23-month-old male with ToF who developed LCOS post-surgery, followed by refractory JET, left atrial thrombus, embolic occipital infarction, and transient cortical blindness. LCOS was defined by elevated lactate, low ScvO₂, hypotension, and oliguria. JET was managed with amiodarone, ivabradine, magnesium, and targeted temperature control. Thrombosis resolved with heparin, yet cortical infarct occurred. Neuroprotective therapy included piracetam and mannitol.OutcomePartial visual recovery was observed by POD-30. Follow-up echocardiography showed improved RV function and resolution of arrhythmia. The patient was discharged on POD-35 with improving neurologic status.ConclusionLCOS can trigger a cascade of cardiac, thrombotic, and neurologic complications. Early recognition and multidisciplinary intervention are essential. This case highlights the potential reversibility of cortical blindness and the importance of comprehensive postoperative surveillance.